Effects of Copper Fungicides Spray on Nutrient Contents in Soils of Cocoa Growing Areas of Southwestern Nigeria - Azeez, Musibau O; Adesanwo, Olusola O; Adepetu, Joseph A (Tanzania Journal of Science, 2021)
The present study aimed at evaluating the effects of copper fungicides spray on physical and chemical properties of soils of cocoa growing areas of southwestern Nigeria. Samples were collected from selected cocoa farms and adjacent plots across three states (9 samples from Osun State, 9 samples from Ondo State and 7 samples from Ekiti State), within rainforest zone of Nigeria. The physical and chemical properties of the soil samples were determined. Copper contents of the cocoa plantation soils were significantly higher (16.23 mg Cu/kg) than the adjacent plots (6.31 mg Cu/kg) indicating accumulation of Cu in the soil because of long-term Cu fungicides spray. Other chemical properties determined (pH, Zn, % organic matter, % total N, Ca, Mg and Na) also had higher values in cocoa plantations compared to adjacent plots. Significant decrease was observed in available P in soil samples from cocoa plantations (24.05 mg P/kg) when compared with adjacent plots (30.36 mg P/kg). Management practices like applications of K and P fertilizers are highly recommended for viable cocoa growth and optimum yield in the study areas. Reduction of canopy formed by cocoa trees will allow easy penetration of sunlight into cocoa plantation thereby increase the rate of organic matter decomposition. Keywords: Copper, fungicide spray, cocoa farms, black pod disease.